Effect of Conservation Management on Oxisol in a Sugarcane Area Under a Pre-Sprouted Seedling System - Oliveira, Ingrid Nehmi de; Souza, Zigomar Menezes de; Bolonhezi, Denizart; Tavares, Rose Luiza Moraes; Lima, Renato Paiva de; Silva, Reginaldo Barboza da [UNESP]; Araújo, Fernando Silva; Lovera, Lenon Henrique; Lima, Elizeu de Souza (MDPI, 2024)
Conservation soil management, such as no-tillage and Rip Strip®, can be developed as an alternative to degradation processes such as compaction. This study aimed to compare conventional and conservation soil tillage regarding their soil physical attributes, root system, and stalk yield for two years. The experiment was conducted on the premises of Fazenda Cresciúma in an area of Typic Eutrudox in the municipality of Jardinópolis, state of São Paulo, Brazil, with an experimental design in random blocks. The treatments evaluated for the transplanted sugarcane were as follows: CT—conventional tillage with disk harrow; CTS—conventional tillage with disk harrow and subsoiling; MT—minimum tillage with Rip Strip®; NT—no-tillage. The variables evaluated were dry root mass, soil bulk density (Bd), total porosity (TP), and stalk yield for sugarcane plant and first ratoon harvest. The results allowed us to observe that CT was the system that most reduced the TP (varying 0.44–0.47 m3 m−3), while MT was the one that presented fewer changes (TP varying 0.47–0.51 m3 m−3). NT obtained the highest stalk yield (123 Mg ha−1) in the sugarcane plant cycle and greater amounts of roots in depths below 0.80 m. Conservation tillage by Rip Strip® proved to be a viable system for use in sugarcane because it provides greater dry root mass on the surface and maintenance of physical attributes compared to conventional tillage.
Keywords: mixed linear models; Rip Strip; soil compaction; strip-till